Physical controls on the formation of halophytic saline substrates near Alexandra, Central Otago, New Zealand. Issue 3 (3rd July 2022) - Craw, Dave; Rufaut, Cathy; Pillai, Dhana; Read, Stephen
ABSTRACT: Soil-free saline substrates near Alexandra have developed from evaporated marine aerosols dominated by NaCl. The salts accumulate on impermeable substrates where there is minimal chemical interaction between water and rock. Most of the known saline sites occur on outcrops of clay-altered schist exposed immediately below the regional Miocene unconformity, and on clay-rich sediments eroded from altered schist. The unconformity zones that host these saline sites occur linearly along structurally controlled depressions. These unconformity zones have been major targets for placer gold mining, and most of the saline sites occur in abandoned mines where impermeable rocks were exposed by historic excavations. Native salt-tolerant plants (halophytes) have colonised parts of the saline substrates, especially on actively-forming clay pans derived from nearby steep mine cuts. Saline sites are ephemeral, as salt is readily removed in water, sediments can bury the surfaces, and incursion of adventive plant species encourages further sedimentation. Erosional disturbance can overcome these effects temporarily, and surface erosion to bare ground along the strike of the structurally controlled schist unconformity zones may also create new saline sites.